El control biológico como estrategia para apoyar las exportaciones agrícolas no tradicionales en Perú: un análisis empírico - Duarte Cueva, Franklin (2012)
The study is oriented to explore the general characteristics of agriculture, the biological control as a pest control mechanism and agro export industry. In this context, we try to promote the use of biological control as a strategy to support nontraditional exports related to products such as asparagus and fresh avocados grown in the La Libertad Department (Peru), through an agronomic and management approach. Biological control is the basis of integrated pest management (IPM) and contributes to the conservation of agricultural ecosystems allowing to export companies reduce costs, fulfill international phytosanitary measures and supports the preservation of the environment and health. Thus, the Peruvian agro export companies could build a sustainable competitive advantage and seek a positioning as socially responsible firms. We analyze variables such as crop statistics, comparative costs between biological control and chemical control, main destination markets for asparagus and fresh avocados, international standards, among others.